Efficiency determination of the laser-induced reaction of NO(A( 2Σ+)) with CO2 - Codnia, Jorge (2011)
The reaction of NO excited in the electronic state A(2Σ +, v′ = 2) with CO2 has been studied. This has been carried on by irradiating NO samples in excess of CO2 with a home-made dye laser pumped by a commercial frequency tripled Nd:YAG laser. The samples have been analyzed by FTIR spectrometry before and after irradiation to obtain the fraction of molecules reacted per pulse. The NO excitation efficiency was determined from the measurement of the absorption cross-section, the sample transmittance and the energy of the laser pulse. A value of (0.26 ± 0.01) was obtained for the reaction efficiency, indicating that about 25% of the excited NO molecules reacted with CO2. A reaction rate constant value of (1.30 ± 0.12) × 10-10 cm3 molecules-1 s-1 was determined from the value of the reaction efficiency obtained in this work and the global electronic quenching rate constant of NO(A2Σ+, v′ = 2) reported by Nee et al. [6 for CO2